An integrated instrumental and sensory approach to describe the effects of chickpea flour, psyllium, and their combination at reducing gluten-free bread staling. (June 2021) - Santos, Fernanda G.; Aguiar, Etiene V.; Braga, Anna Rafaela C.; Alencar, Natália M.M.; Rosell, Cristina M.; Capriles, Vanessa D.
Graphical abstract: Highlights: Gluten-free bread (GFB) staling was studied by an instrumental and sensory approach. Chickpea flour reduced moisture loss and crumb hardness during 7 days of storage. Consumers described chickpea-based GFB as soft and fresh during storage. Consumers with gluten-related disorders considered chickpea-psyllium-based GFB ideally soft. Chickpea flour and its combination with psyllium reduced and delayed GFB staling. Abstract: Gluten-free bread (GFB) is generally recognized as a product with a less than satisfying appearance, texture, and mouthfeel that lacks nutritional quality and has a short shelf life. In this sense, the potential of chickpea flour (CF), psyllium (PSY), and their combination at reducing GFB staling were investigated in comparison to control bread prepared with rice flour (RF) and cassava starch (75:25 flour weight basis). The effect of time on the crumb and crust moisture and texture and loaves sensory parameters (acceptability on a 9-point structured hedonic scale, Just-About-Right level for bread softness, sensory profile by Check-All-That-Apply) was assessed during 7 days of storage. Replacing RF with CF reduced moisture loss and crumb hardening not only on the same day of baking but also after 7 days of storage. PSY addition (5.5 % flour weight basis) delayed the loss of cohesiveness and springiness of crumb during storage. The findings suggest that CF, and its combination with PSY, was promising for reducing and delaying GFB staling, thus maintaining acceptability, softness, and freshness after 7 days of storage, according to the perceptions of consumers.